S-nitrosylated fetal hemoglobin in neonatal human blood - Riccio, Daniel A. (Biochem Biophys Res Commun, 2016)
BACKGROUND: Nitric oxide (NO) and its derivatives play important roles in the cardiopulmonary transition upon birth and in other oxygen-sensitive developmental milestones. One mechanism for the coupling of oxygen sensing and signaling by NO species is via the formation of an S-nitrosothiol (SNO) moiety on hemoglobin (Hb, forming SNO-Hb) and its release from the red blood cell in hypoxia. Although SNO-Hb formed on adult-type Hb (HbA, forming SNO-HbA) has been documented in physiological and pathophysiological human states, the fetal variant, SNO-HbF, has thus far not been isolated or characterized in human blood. METHODS AND RESULTS: We developed a technique capable of separating Hbs A and F under conditions that preserve SNO. We then measured SNO-HbF in the blood of healthy and premature or otherwise ill neonates using the gold standard for SNO measurement, mercury-coupled photolysis-chemiluminescence. SNO-HbF levels were in the range of those previously reported for HbA in adults. We found that SNO-HbF was more abundant at earlier gestational age (<30 weeks), even when accounting for the absolute HbF level. CONCLUSIONS: The ability to monitor SNO-HbF could provide new insights into fetal development and the perinatal transition, and has potential as a biomarker relevant to the management of neonatal diseases.